STUDENT’S PERCEPTION OF ADMINISTRATIVE TECHNOLOGY COURSES IN OFFICE ADMINISTRATION EDUCATION STUDY PROGRAM - Sri Yunita Simanjuntak; Muh. Nasrullah; Muh. Darwis (Yayasan Amanah Nur Aman, 2026)
This study aims to determine how students perceive the administrative technology course in the Office Administration Education study program. This study applies a qualitative descriptive approach. This study was conducted online by involving students from the Office Administration Education study program, Makassar State University, semester 3. Dominant students use Google Meet in the implementation of online lectures, then in the implementation of each material, the most preferred lecture material by students is the technology ethics material, then the least preferred material by students is the Decision support system. Then the use of Microsoft Office oord is widely used for correspondence practice, Excel for making financial reports and PowerPoint / Canva for making presentations. The use of word clouds that are most widely used by students is Google Drive and the implementation of lecture evaluations, students predominantly like the use of the quiziz application.